2022
DOI: 10.2174/1871527320666211201160001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antidepressant-like Effect of Chronic Administration of Nigella Fixed Oil Versus Fluoxetine in Rats

Abstract: Background: Depression is a group of syndromes characterized by notable and persistent mood disorders, and is one of the most prevalent psychiatric disorders, while the existing treatments have an altered risk-benefit balance. The therapeutic properties of Nigella have been confirmed, suggesting the reliance on phytotherapy. The objective of the present paper is to investigate the antidepressive-like effect of Nigella sativa on rats exposed to the Unpredictable Chronic Mild Stress procedure. Methods: Wistar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…In the present study, we found that chronic treatment with NS significantly increased sucrose consumption in male and female naïve rats (Figure 2), which is suggestive of a potent hedonic-like effect. Together with the results of previous studies in animals [9,11,61,62,95], our findings further strengthen the pro-hedonic/antidepressant potential of NS treatment. A strong testimony to the antidepressant potential of NS came from a randomized clinical trial of patients with depression [96].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In the present study, we found that chronic treatment with NS significantly increased sucrose consumption in male and female naïve rats (Figure 2), which is suggestive of a potent hedonic-like effect. Together with the results of previous studies in animals [9,11,61,62,95], our findings further strengthen the pro-hedonic/antidepressant potential of NS treatment. A strong testimony to the antidepressant potential of NS came from a randomized clinical trial of patients with depression [96].…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies that investigated the behavioral effects of NS in animal models mainly focused on its antidepressant and anxiolytic potential revealing positive therapeutic outcomes [9,11,61,62,95]. In the present study, we found that chronic treatment with NS significantly increased sucrose consumption in male and female naïve rats (Figure 2), which is suggestive of a potent hedonic-like effect.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations